2017
DOI: 10.1007/s00192-017-3345-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes with the retropubic tension-free vaginal tape (TVT) procedure compared to Burch colposuspension for correcting stress urinary incontinence (SUI)

Abstract: The long-term efficacy of TVT surgery was superior to that of Burch colposuspension in women with SUI. In addition, the rate of late prolapse surgery was significantly higher after the Burch procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
4
8
0
2
Order By: Relevance
“…Urinal bladder perforation is one of the most common intraoperative complications. Studies have demonstrated this in 0.7-24% of TVT procedures [17,[21][22][23]. Our result is consistent with the one reported by Ford et al [9] (4.5%), who analysed 8,652 TVT procedures.…”
Section: Discussionsupporting
confidence: 93%
“…Urinal bladder perforation is one of the most common intraoperative complications. Studies have demonstrated this in 0.7-24% of TVT procedures [17,[21][22][23]. Our result is consistent with the one reported by Ford et al [9] (4.5%), who analysed 8,652 TVT procedures.…”
Section: Discussionsupporting
confidence: 93%
“…In a nationwide cohort study, Foss Hansen and colleagues reported, that Burch colposuspension MUS had a similar risk of reoperation (6%) . Another study conducted by Holdø and colleagues showed a significantly lower cumulative rate of recurrence up to 12 years after retropubic MUS than after Burch colposuspension . Manca and colleagues performed a cost‐utility analysis comparing tension‐free vaginal tape and open Burch colposuspension .…”
Section: Methodsmentioning
confidence: 99%
“…49 Another study conducted by Holdø and colleagues showed a significantly lower cumulative rate of recurrence up to 12 years after retropubic MUS than after Burch colposuspension. 50 Manca and colleagues performed a cost-utility analysis comparing tension-free vaginal tape and open Burch colposuspension. 51 They found that, over a postoperative period of six months, there were no significant differences in terms of cost-efficiency between retropubic MUS and Burch colposuspension.…”
Section: Open Burch Colposuspension and Midurethral Slingsmentioning
confidence: 99%
“…Kirurgi i bukhule og bekken har endret seg betydelig de siste tiårene, med økende andel laparoskopi (inkludert robotkirurgi) som erstatning for laparotomi (9, 10) samt bruk av nett og slynger ved urininkontinens og genitalprolaps (11,12), noe som kan påvirke risikoen og mønsteret for fistelutvikling. Strålebehandling er fortsatt en aktuell behandlingsform, saerlig ved anorektal og cervikal kreft (13).…”
Section: Fortolkningunclassified
“…Kvinnene ble fulgt med etterkontroller til fistelen var bekreftet lukket eller man ikke anså å ha ytterligere fistelrettet behandling å tilby. Tensjonsfri vaginaltape er den vanligste operasjonen ved stressinkontinens (11). Totalt 9 % av fistler etter kirurgi i vårt materiale var forårsaket av tensjonsfri vaginaltape.…”
Section: Diagnostiske Og Kirurgiske Prosedyrerunclassified